Old English studies in honour of John C. Pope - Pope, John Collins, 1904-; Burlin, Robert B., 1928-; Irving, Edward Burroughs, 1923- (University of Toronto Press, 1974)
As a tribute to the superb teaching and exemplary literary criticism of this eminent Yale scholar, the majority of these essays deal with thematic, textual, and prosodic issues in Old English poetry, seven of them providing a valuable reassessment of some of the perennial problems of Beowulf criticism: the implications of its metaphysical and social systems as well as its rhetorical and imagistic structures; and especially the recurrent need for a careful re-examination of the text and a return to the manuscript evidence. These contributions add significantly to the debate over the meaning of the tragic element of Beowulf and to the better understanding of the character of its hero. The poetic literature is further represented by a new evaluation of the central literary problems of the Exodus, a reinterpretation of the puzzling Wulf and Eadwacer, and philological and syntactical examinations of Maldon and the Phoenix. Other interests of Professor Pope are reflected in two metrical analyses and a thorough lexicographical survey of Old English prosodic terminology, a painstaking study of the chapter-headings in the Old English Bede, and an essay which brilliantly establishes the experience of a hitherto unknown Ælfric manuscript.